How to compare market efficiency? The Sharpe ratio based on the ARMA-GARCH forecast - Lin Liu; Qiguang Chen (Financial Innovation, 2020)
This paper derives a new method for comparing the weak-form efficiency of markets. The author derives the formula of the Sharpe ratio from the ARMA-GARCH model and finds that the Sharpe ratio just depends on the coefficients of the AR and MA terms and is not affected by the GARCH process. For empirical purposes, the Sharpe ratio can be formulated with a monotonic increasing function of R-squared if the sample size is large enough. One can utilize the Sharpe ratio to compare weak-form efficiency among different markets. The results of stochastic simulation demonstrate the validity of the proposed method. The author also constructs empirical AR-GARCH models and computes the Sharpe ratio for S&P 500 Index and the SSE Composite Index.
Keywords: G10; G14; G17; C22; 650; ARMA; GARCH; Measurement of market efficiency; Sharpe ratio; Stochastic simulation